Reflexões Sobre o Acesso a Museus e Instituições Culturais (Palíndromo, 2013)
This article is a part of master's research, "Crianças, museus e formação de público em São Paulo" made at UNESP in 2011. In the text we talk about access to museums and cultural institutions. We started with the speech of children and then we based some authors to reflect on how people come or not come to museums. More than think only in material issue, this paper proposes think access as choice and potentiality.
Keywords: Museum; Access; Public